Isolasi dan Identifikasi Senyawa Flavonoid dari Daun Murbei (Morus alba Linn) - Mabruroh, Eva Qomariyah; Mursiti, Sri; Kusumo, Ersanghono (Indonesian Journal of Chemical Science, 2019)
Mulberry leaves are used as traditional medicine because they contain secondary metabolites. Mulberry leaves are used as traditional medicine because they contain secondary metabolites. The purpose of this research is to know determine isolation method, identification, and class of flavonoid compounds from mulberry leaves. Sample were isolated using maceration method, liquid partition, gravitation column chromatography (GCC) technical, compound identification using FTIR and UV-Vis. Extraction of 3000 g dry powder of mulberry leaves using maceration method with n-hexane and ethanol solvent during 3x24 hours yielded 82.3538 g dark green ethanol extract, the phytochemical test showed that contained flavonoid compound. The ethanol extract was extracted with liquid partition using ethyl acetate: aquades (1 : 1) yielded 38.4253 g ethyl acetate extract, that was TLC test eluted with n-hexane : ethyl acetate was obtained by the best eluent of  8:2. Isolation using column chromatography with silica gel and n-hexane: ethyl acetate eluent (9:1), (8:2), (7:3), and (6:4) gave 7 fractions, the phytochemical test showed that contained strong intensity flavonoid compound. Analysis of fraction 7 isolate using FTIR and UV-Vis. Infrared analysis showed that the isolate had bound -OH, CH aliphatic, C=O carbonil, C=C aromatic, CO alcohol, and CH aromatic groups. Analysis of fraction 7 isolate using UV-Visible gained 2 peaks at λ 324 nm (band I) and λ 291 nm (band II) which indicated the flavonoide groups of flavanone or dihydroflavonol. By using shifting reagent the fraction 7 isolate was suggested to contain dihydroflavonol group with substituent of ortho-dihydroxyl group on C-6 and C-7, ortho-dihydroxyl group on C-4 'and C-5', and hydroxyl group on C-3.